1996
DOI: 10.1063/1.363186
|View full text |Cite
|
Sign up to set email alerts
|

Ion damage buildup and amorphization processes in GaAs–AlxGa1−xAs multilayers

Abstract: The nature of ion damage buildup and amorphization in GaAs–AlxGa1−xAs multilayers at liquid-nitrogen temperature is investigated for a variety of compositions and structures using Rutherford backscattering-channeling and cross-sectional transmission electron microscopy techniques. In this multilayer system, damage accumulates preferentially in the GaAs layers; however, the presence of AlGaAs enhances the dynamic annealing process in adjacent GaAs regions and thus amorphization is retarded close to the GaAs–AlG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 34 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…The damage peak at about 0.25 ps is roughly 10 times higher for PF 4 and 7 times higher for PF 2 than the final damage after the cascade has cooled down. This recombination value (∼10) is 2-3 times higher than in Si [21] and GaAs [105] but much less than in metals; for instance in Fe typical values are ∼50 [106]. There is a second peak in case of PF 4 and Ag projectiles (Figure 6.2).…”
Section: Comparative Study Of Atomic and Molecular Projectilesmentioning
confidence: 91%
“…The damage peak at about 0.25 ps is roughly 10 times higher for PF 4 and 7 times higher for PF 2 than the final damage after the cascade has cooled down. This recombination value (∼10) is 2-3 times higher than in Si [21] and GaAs [105] but much less than in metals; for instance in Fe typical values are ∼50 [106]. There is a second peak in case of PF 4 and Ag projectiles (Figure 6.2).…”
Section: Comparative Study Of Atomic and Molecular Projectilesmentioning
confidence: 91%
“…Interaction between irradiation-induced point defects may cause their annihilation and removal along interfaces and/or surfaces that function as a sink [16]. One should note that AlGaAs has shown a strong dynamic annealing effect, which protects the adjacent GaAs region from ion damages [50]. However for our GaAs/AlGaAs core-shell NWs, the dynamic annealing effect of the AlGaAs shell may not be as significant due to the small thickness (20-70 nm) [33,51].…”
Section: Discussionmentioning
confidence: 97%
“…Hence, there should be further experiments to investigate NWs with diameter down to a few nanometers. One point that should be noted is that previous study has found defect density to be higher in GaAs than AlGaAs [56] due to enhanced dynamic annealing in the latter. This dynamic annealing could even be more efficient at the interface of GaAs-AlGaAs.…”
Section: Ion Irradiation Effect On Horizontally Dispersed Nw Plmentioning
confidence: 92%